Majocchi’s Granuloma after Topical Corticosteroids Therapy - Fu-qiu Li; Sha Lv; Jian-xin Xia (Case Reports in Dermatological Medicine)
Majocchi’s granuloma (MG) is an unusual but not rare dermatophyte infection of dermal and subcutaneous tissues. Dermatophytes usually result in the infections of hair, epidermis, and nail, and are rarely involved in deep cutaneous and subcutaneous tissues. Now it is considered that MG includes two forms: one is a small perifollicular papular form and the other is a deep subcutaneous nodular form; the front one mainly occurs in healthy individuals and the latter one usually presents in immunocompromised hosts. The clinical manifestations of MG are many and varied, except the common presentations of erythema, papule and nodules, and Kaposi sarcoma-like and molluscum-like lesions have been reported in literatures (Kim et al. (2011), Bord et al. (2007), and Lillis et al. (2010)). This characteristic induces the difficulty of diagnosis, and thus it is so important and necessary to make direct microscopical and histological examinations. We describe a case of MG over the face in a patient who had been treated with topical corticosteroids over a long time.